2009
DOI: 10.1097/wnr.0b013e3283306854
|View full text |Cite
|
Sign up to set email alerts
|

Developmental correlation of diffusion anisotropy with auditory-evoked response

Abstract: White matter diffusion anisotropy in the acoustic radiations of the auditory pathway was characterized as a function of development in children and adolescents. Auditory-evoked neuromagnetic fields were also recorded from the same individuals, and the latency of the left and right superior temporal gyrus auditory response of approximately 100 ms was also obtained. White matter diffusion anisotropy increased with age. There was a commensurate shortening of the auditory-evoked response latency with increased age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
42
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 20 publications
6
42
1
Order By: Relevance
“…Taken together, present findings support a line of reasoning that considers M100 peak latency as a marker for autism spectrum disorders, perhaps secondary to abnormal white matter development of the acoustic radiations [14] or other local cortical circuitry abnormalities. Along this line of reasoning, Verhoeven et al [15] recently reported reduced fractional anisotropy in the superior longitudinal fasciculus of patients with specific language impairment but not those with autism spectrum disorder and language impairment when compared to healthy controls.…”
Section: Discussionsupporting
confidence: 83%
“…Taken together, present findings support a line of reasoning that considers M100 peak latency as a marker for autism spectrum disorders, perhaps secondary to abnormal white matter development of the acoustic radiations [14] or other local cortical circuitry abnormalities. Along this line of reasoning, Verhoeven et al [15] recently reported reduced fractional anisotropy in the superior longitudinal fasciculus of patients with specific language impairment but not those with autism spectrum disorder and language impairment when compared to healthy controls.…”
Section: Discussionsupporting
confidence: 83%
“…Recent ERP studies have shown relationships between the magnitude of the brain’s electrophysiological response and white matter microstructure (Westlye et al, 2009; Colrain et al, 2011). Our data strengthen the view that the microstructure of white matter fiber tracts subserving the N400 generators may impact the nature of the N400 response, perhaps by facilitating efficient neuronal conduction (Peters, 2009; Roberts et al, 2009). P300 latencies have been found to be associated more with white matter connectivity than the gray matter volume (Cardenas et al, 2005), and our results indicate that similar relationships may hold for the strength of N400 response.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, observation of a M50 response in all groups likely reflects development of cortical layers III and IV, with the delayed M50 latency in both ASD groups perhaps indicating slower maturation of these layers, perhaps due to delayed myelination of thalamo-cortical pathways in ASD (Roberts et al, 2009, 2013). Lack of a M100 in the young ASD − LI and ASD + LI groups may indicate delayed maturation of layer II and upper layer III in ASD with abnormally decreased synchronization of afferent activity arriving at the synapses in layer II and upper layer III resulting in a greatly desynchronized M100 (Ponton and Eggermont, 2001).…”
Section: Discussionmentioning
confidence: 49%